Association of Anterior Cruciate Ligament Width With Anterior Knee Laxity - Wang, Hsin-Min (J Athl Train, 2016)
CONTEXT: : Greater anterior knee laxity (AKL) has been identified as an anterior cruciate ligament (ACL) injury risk factor. The structural factors that contribute to greater AKL are not fully understood but may include the ACL and bone geometry. OBJECTIVE: : To determine the relationship of ACL width and femoral notch angle to AKL. DESIGN: : Cross-sectional study. SETTING: : Controlled laboratory. PATIENTS OR OTHER PARTICIPANTS: : Twenty recreationally active females (age = 21.2 ± 3.1 years, height = 1.66.1 ± 7.3 cm, mass = 66.5 ± 12.0 kg). MAIN OUTCOME MEASURE(S): : Anterior cruciate ligament width and femoral notch angle were obtained with magnetic resonance imaging of the knee and AKL was assessed. Anterior cruciate ligament width was measured as the width of a line that transected the ACL and was drawn perpendicular to the Blumensaat line. Femoral notch angle was formed by the intersection of the line parallel to the posterior cortex of the femur and the Blumensaat line. Anterior knee laxity was the anterior displacement of the tibia relative to the femur (mm) at 130 N of an applied force. Ten participants' magnetic resonance imaging data were assessed on 2 occasions to establish intratester reliability and precision. Using stepwise backward linear regression, we examined the extent to which ACL width, femoral notch angle, and weight were associated with AKL. RESULTS: : Strong measurement consistency and precision (intraclass correlation coefficient [2,1] ± SEM) were established for ACL width (0.98 ± 0.3 mm) and femoral notch angle (0.97° ± 1.1°). The regression demonstrated that ACL width (5.9 ± 1.4 mm) was negatively associated with AKL (7.2 ± 2.0 mm; R(2) = 0.22, P = .04). Femoral notch angle and weight were not retained in the final model. CONCLUSIONS: : A narrower ACL was associated with greater AKL. This finding may inform the development of ACL injury-prevention programs that include components designed to increase ACL size or strength (or both). Future authors should establish which other factors contribute to greater AKL in order to best inform injury-prevention efforts.